Order Parameters in XXZ-Type Spin 1/2 Quantum Models with Gibbsian Ground States - Skrypnik, W. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
A class of general spin 1/2 lattice models on hyper-cubic lattice Zd, whose Hamiltonians are sums of two functions depending on the Pauli matrices S¹, S² and S³, respectively, are found, which have Gibbsian eigen (ground) states and two order parameters for two spin components x, z simultaneously for large values of the parameter α playing the role of the inverse temperature. It is shown that the ferromagnetic order in x direction exists for all dimensions d ≥ 1 for a wide class of considered models (a proof is remarkably simple).